RECORDS OF LICHEN SPECIES FROM GENUS ACAROSPORA, NEW FOR SERBIA, SOUTHWEST BALKAN PENINSULA - Aleksić, Gordana; Vasić, Predrag; Jakšić, Tatjana (Bulletin of Natural Sciences Research, 2023)
The lichens: Acarospora impressula, A. nitrophila, A. nodulosa, A. schleicheri, A. sinopica, A. smaragdula and A. umbillicata, collected in North Kosovo are reported as a new species to Serbia, following a recent lichenological survey. Location, herbarium deposits and substrates are given, together with notes on distribution of the reported taxa.
Keywords: Lichens; New records; Biodiversity; Genus Acarospora; R. Serbia